Using English Songs to Motivate the Senior High School Students to Learn English Vocabulary - Yanti, Nur; Dollah, Syarifuddin; G., Hasriani (State University of Makassar, 2024)
This study aims to find out how English teachers use song to motivate students to learn English. This research took place at SMA Negeri 27 Bone, Bone regency, South Sulawesi. The participants taken by the researchers were students of class XI IPA, with a total of 7 students. Researchers used a qualitative descriptive method with a purposive sampling technique in selecting participants. The research instruments were observation and interviews. Based on the results of observations and interviews, the researchers found that students were very enthusiastic when learning while listening to songs and their vocabulary increased because they found many new words in the lyrics of the song, as a result they were very motivated again to learn English. Furthermore, the researcher concluded that learning English using song media can increase students' motivation and increase their vocabulary. Keywords— Motivation, Vocabulary and Songs Media